PELUANG GOAL SHOOTING TEKNIK FLYING SHOT DAN STANDING THROW SHOT PADA PERMAINAN BOLA TANGAN - Wiwik Susanti; Andika Triansyah; Mimi Haetami (Universitas Tanjungpura, 2020)
AbstractThe problem in this research is flying shot technique and standing throw shot are the most used technique to create goals, but both of this techniques can often be failed by the opponents and there are no statistical records regarding the opportunity for goals using the flying shot technique and standing throw shot. This research aims to determine the opportunities for goal shooting in handball playing by using flying shot technique and standing throw shot. This researh is a research that use quantitative descriptive method, with survey research. This research uses several steps, that are data collection and data calculation. The sample in this research were handball athletes in West Kalimantan Province who supported by 10 people. The results of the goal scoring obtained in the standing throw tehnique were 14,44% while using the flying shot technique were 21,11%, compared to the standing shot technique and flying shot, the flying shot technique was more likely to create a goal, that was 6,67%. So it can be conclude that flying shot technique more likely to create goals than the standing throw shot. Keywords: Goal shooting, Handball